Stainless steel for fuel cell separators with excellent surface electrical conductivity and corrosion resistance
Patent Information
- Application Number
- JP2023535010
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-11-24
- Filing Date
- 2021-12-08
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2041-12-08
AI Technical Summary
【0024】 本発明は、ステンレス鋼の表面に形成される半導体的特性を有する表面酸化物層を導体化して燃料電池分離板用途の素材に適用可能な表面貫通電気伝導性及び耐食性に優れた燃料電池分離板用ステンレス鋼を提供することができる。
Smart Images

Figure 0007640699000015 
Figure 0007640699000016 
Figure 0007640699000017
Abstract
Description
[Technical field]
[0001] The present invention relates to a stainless steel having excellent through-surface electrical conductivity and corrosion resistance and a manufacturing method thereof, and more particularly to a stainless steel for a fuel cell separator having excellent through-surface electrical conductivity and corrosion resistance. [Background technology]
[0002] Stainless steel has excellent corrosion resistance and is easy to process, and is therefore being considered for use as a material for electronic components and fuel cell separators. However, ordinary stainless steel has a problem in that the passive film on the surface acts as a through-plane resistance element, making it difficult to ensure sufficient electrical conductivity.
[0003] To date, the mechanism of the effect of the passive film on the trans-surface electrical conductivity of stainless steel has not been clearly elucidated. In order to improve the trans-surface electrical conductivity of the passive film, Ni plating has been performed in the case of materials for electronic components, and a process of coating the surface of stainless steel with a conductive material such as gold, carbon, or nitride has been proposed in order to reduce the high contact resistance of stainless steel in the case of fuel cell separators. However, there are problems in that the additional process of coating with Ni plating or other coating materials increases manufacturing costs and time, reducing productivity, and there is also a problem in that the fundamental trans-surface resistance of the passive film cannot be reduced.
[0004] As another method for improving the surface electrical conductivity of stainless steel, methods for modifying the surface of stainless steel have been attempted.
[0005] Patent Document 1 proposes a stainless steel for a separator plate having low interfacial contact resistance and high corrosion potential by controlling a surface modification process.
[0006] Patent Document 2 presents a method for producing stainless steel having excellent corrosion resistance and low contact resistance by immersing stainless steel containing 17 to 23 wt % Cr in a [HF]≧[HNO3] solution.
[0007] Patent Document 3 presents a stainless steel containing 15-45% by weight of Cr and 0.1-5% by weight of Mo, in which the atomic ratio of Cr to Fe contained in the passive film is 1 or more. However, Patent Documents 1 to 3 have the limitation that they are unable to reduce the fundamental penetration resistance of the passive film of stainless steel by adjusting only the ratio of the number of Cr / Fe atoms in the passive film within a region of several nm. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 10-2014-0081161 [Patent Document 1] Korean Patent Publication No. 10-2013-0099148 [Patent Document 1] JP 2004-149920 A Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a stainless steel for fuel cell separators that has excellent through-surface electrical conductivity and corrosion resistance and can be used as a material for fuel cell separators. [Means for solving the problem]
[0010] As a means for achieving the above-mentioned object, one example of the present invention provides a stainless steel having excellent through-surface electrical conductivity and corrosion resistance, characterized in that, when the surface of the stainless steel containing 15% by weight or more of Cr is measured by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source at a photoelectron take-off angle of 12°, the measured surface oxide element ratio (1) value is 0.5 to 5, and the measured surface oxide element ratio (2) value is 0.5 or less.
[0011] TIFF0007640699000001.tif16134
[0012] TIFF0007640699000002.tif16134
[0013] Here, the Cr oxide means Cr3O4, Cr2O3, CrO2 or CrO3, the Cr hydroxide means CrOOH, Cr(OH)2 or Cr(OH)3, the Fe oxide means FeO, Fe2O3 or Fe3O4, and the Fe hydroxide means FeOOH.
[0014] The total oxides and hydroxides include the Cr oxides, the Cr hydroxides, the Fe oxides, the Fe hydroxides, and metal oxides (MOs), and the metal oxides (MOs) include mixed oxides, where M is Ti, Nb, Mn, Si, V, or a combination thereof excluding Cr and Fe, and O means oxygen.
[0015] In the stainless steel for a fuel cell separator plate of the present invention having excellent through-surface electrical conductivity and corrosion resistance, the band gap energy of a surface oxide layer of the stainless steel may be 2 eV or less.
[0016] In the stainless steel for a fuel cell separator having excellent through-surface electrical conductivity and corrosion resistance according to the present invention, the surface oxide layer of the stainless steel can form an ohmic contact with the base material.
[0017] In the stainless steel for a fuel cell separator of the present invention having excellent through-surface electrical conductivity and corrosion resistance, the surface passivation potential of the stainless steel may be 0.2 V or more.
[0018] An incubation step in which the surface of the stainless steel cold-rolled sheet is modified using an acid solution for a process time that satisfies the following formula (1); and
[0019] The surface may be modified by a passivation step for a process time satisfying the following formula (2):
[0020] (1) Incubation process time (seconds) ≧3x[Mn]+15x[Si+Ti]+10x[Nb+V]-0.05x[Cr]
[0021] (2) Passivation process time (seconds) ≧0.8x[Cr]
[0022] In the above formula, Mn, Si, Ti, Nb, V, and Cr are values in weight percent.
[0023] In the method for manufacturing a stainless steel for a fuel cell separator having excellent through-surface electrical conductivity and corrosion resistance according to an embodiment of the present invention, the acid solution may include one or more of sulfuric acid, nitric acid, hydrochloric acid, ammonium fluoride, hydrogen peroxide, and citric acid. Effect of the Invention
[0024] The present invention can provide a stainless steel for fuel cell separators that has excellent through-surface electrical conductivity and corrosion resistance and is applicable to materials for fuel cell separators by converting a surface oxide layer having semiconducting properties that is formed on the surface of the stainless steel into a conductor. [Brief description of the drawings]
[0025] [Figure 1] 13 shows the results of comparing the band gap energies of the surface oxide layers for Example 6 and Comparative Example 6. [Diagram 2] FIG. 13 is a diagram showing the incubation step time and the passivation step time for Example 6. The passivation step time is the time during which the potential increases and is maintained from the time when the surface potential becomes 0.2 V (vs. saturated calomel electrode) or more. [Diagram 3] FIG. 13 is a diagram showing the incubation process time and the passivation process time for Comparative Example 6. [Figure 4]1 shows the results of observing Si, Mn, Nb, and V oxides when the surface of Example 6 is measured by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source at a photoelectron takeoff angle of 12°. [Diagram 5] 1 shows the results of observing oxides of Si, Mn, Nb, and V when the surface of Comparative Example 6 is measured by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source at a photoelectron takeoff angle of 12°. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] As a means for achieving the above-mentioned object, a stainless steel having excellent through-surface electrical conductivity and corrosion resistance according to one embodiment of the present invention may have a surface oxide element ratio (1) value of 0.5 to 5 and a surface oxide element ratio (2) value of 0.5 or less when the surface of the stainless steel containing 15% by weight or more of Cr is measured by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source at a photoelectron take-off angle of 12°.
[0027] TIFF0007640699000003.tif16134
[0028] TIFF0007640699000004.tif16134
[0029] Here, the Cr oxide means Cr3O4, Cr2O3, CrO2 or CrO3, the Cr hydroxide means CrOOH, Cr(OH)2 or Cr(OH)3, the Fe oxide means FeO, Fe2O3 or Fe3O4, and the Fe hydroxide means FeOOH.
[0030] The total oxides and hydroxides include the Cr oxides, the Cr hydroxides, the Fe oxides, the Fe hydroxides, and metal oxides (MOs), and the metal oxides (MOs) include mixed oxides, where M is Ti, Nb, Mn, Si, V, or a combination thereof excluding Cr and Fe, and O means oxygen.
[0031] According to one embodiment of the present invention, a stainless steel having excellent through-surface electrical conductivity and corrosion resistance may have a surface oxide element ratio (1) value of 0.5 to 5 and a surface oxide element ratio (2) value of 0.5 or less when the surface of the stainless steel containing 15% by weight or more of Cr is measured by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source at a photoelectron take-off angle of 12°.
[0032] TIFF0007640699000005.tif16134
[0033] TIFF0007640699000006.tif16134
[0034] Here, the Cr oxide means Cr3O4, Cr2O3, CrO2 or CrO3, the Cr hydroxide means CrOOH, Cr(OH)2 or Cr(OH)3, the Fe oxide means FeO, Fe2O3 or Fe3O4, and the Fe hydroxide means FeOOH.
[0035] The total oxides and hydroxides include the Cr oxides, the Cr hydroxides, the Fe oxides, the Fe hydroxides, and metal oxides (MOs), and the metal oxides (MOs) include mixed oxides, where M is Ti, Nb, Mn, Si, V, or a combination thereof excluding Cr and Fe, and O means oxygen.
[0036] In the stainless steel for a fuel cell separator plate of the present invention having excellent through-surface electrical conductivity and corrosion resistance, the band gap energy of a surface oxide layer of the stainless steel may be 2 eV or less.
[0037] In the stainless steel for a fuel cell separator having excellent through-surface electrical conductivity and corrosion resistance according to the present invention, the surface oxide layer of the stainless steel can form an ohmic contact with the base material.
[0038] In the stainless steel for a fuel cell separator of the present invention having excellent through-surface electrical conductivity and corrosion resistance, the surface passivation potential of the stainless steel may be 0.2 V or more.
[0039] In the following, preferred embodiments of the present invention will be described. However, the embodiments of the present invention may be modified into various other forms, and the technical concept of the present invention is not limited to the embodiments described below. Furthermore, the embodiments of the present invention are provided to more completely explain the present invention to those having average knowledge in the art.
[0040] The terms used in this application are only used to describe specific examples. For example, singular expressions include plural expressions unless the context clearly requires the singular. In addition, it should be noted that the terms "comprise" or "comprise" used in this application are used to clearly indicate the presence of features, steps, functions, components, or combinations thereof described in the specification, and are not used to preliminarily exclude the presence of other features, steps, functions, components, or combinations thereof.
[0041] Meanwhile, unless otherwise defined, all terms used herein should be considered to have the same meaning as that commonly understood by a person having ordinary skill in the art to which the present invention belongs. Therefore, unless clearly defined herein, specific terms should not be interpreted as having an overly ideal or formal meaning. For example, in this specification, singular expressions include plural expressions unless there is a clear exception in the context.
[0042] In addition, in this specification, the terms "about," "substantially," and the like are used in the sense of a numerical value or close to a numerical value when the tolerances of manufacturing and materials inherent in the referred meaning are presented, and are used to prevent unconscionable infringers from unfairly exploiting the disclosure in which precise or absolute numerical values are referred to in order to aid in the understanding of the present invention.
[0043] In addition, in this specification, "stainless cold-rolled steel sheet" means a stainless cold-rolled steel sheet manufactured by a typical stainless steel manufacturing process of hot rolling-heating-cold rolling-annealing, and may be interpreted as a stainless cold-rolled steel sheet manufactured by a typical stainless cold-rolled steel sheet manufacturing process within the scope that a person of ordinary skill in the relevant technical field would obviously recognize.
[0044] In addition, in this specification, the term "surface oxide" refers to an oxide formed on the surface of stainless steel when the stainless steel is exposed to a temperature of about 200°C or less and the base metal element is spontaneously oxidized by external oxygen. The surface oxide is mainly composed of Cr2O3 and may include, for example, SiO2, SiO, SiO3, MnO, MnO2, Mn2O3, VO, V2O3, V2O5, NbO, NbO2, Nb2O5, TiO2, FeO, Fe2O3, Fe3O4, etc. Although examples of surface oxides are listed above, it should be noted that these are examples to help understand the present invention and do not particularly limit the technical idea of the present invention.
[0045] Furthermore, in this specification, the term "surface oxide layer" refers to a layer containing a surface oxide of the present invention, and may also be interpreted as a passive film on stainless steel.
[0046] In addition, in this specification, "Fe oxide" refers to all Fe oxides in oxide form, such as FeO, Fe2O3, Fe3O4, etc., within the scope that a person of ordinary skill in the art can obviously recognize. "Fe hydroxide" refers to FeOOH, Fe(OH) 2- , Fe(OH)3, and the like, means all Fe hydroxides in hydroxide form within the scope that a person of ordinary skill in the art in the relevant technical field can obviously recognize.
[0047] In addition, in this specification, "Cr oxide" refers to all Cr oxides in oxide form, such as Cr3O4, Cr2O3, CrO2, CrO3, etc., within the scope that a person skilled in the art would recognize obviously. "Cr hydroxide" refers to all Cr hydroxides in hydroxide form, such as CrOOH, Cr(OH)2, Cr(OH)3, etc., within the scope that a person skilled in the art would recognize obviously.
[0048] The surface oxide of a typical stainless steel passive film is mainly composed of Cr2O3 and contains SiO2, SiO, SiO3, MnO, MnO2, Mn2O3, VO, V2O3, V2O5, NbO, NbO2, Nb2O5, TiO2, FeO, Fe2O3, Fe3O4, etc., and is known to have high resistance due to the semiconducting properties of these oxides. The inventors of the present invention have discovered that by controlling the content ratio of the component elements of the surface oxide layer so that the band gap energy of the stainless steel surface oxide layer is controlled to 2 eV or less and the surface corrosion potential is controlled to 0.2 V or more based on a saturated calomel electrode, the surface oxide layer becomes a conductor, resulting in excellent surface corrosion resistance, and that a stainless steel for a fuel cell separator with excellent surface through-hole electrical transmission and corrosion resistance that can be used as a material for a battery separator is found.
[0049] According to one example of the present invention, the stainless steel having excellent through-surface electrical conductivity and corrosion resistance according to one example of the present invention may have a surface oxide element ratio (1) value of 0.5 to 5 and a surface oxide element ratio (2) value of 0.5 or less when the surface of the stainless steel containing 15% by weight or more of Cr is measured by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source at a photoelectron take-off angle of 12°.
[0050] TIFF0007640699000007.tif16134
[0051] TIFF0007640699000008.tif16134
[0052] Here, the Cr oxide means Cr3O4, Cr2O3, CrO2 or CrO3, the Cr hydroxide means CrOOH, Cr(OH)2 or Cr(OH)3, the Fe oxide means FeO, Fe2O3 or Fe3O4, and the Fe hydroxide means FeOOH.
[0053] The total oxides and hydroxides include the Cr oxides, the Cr hydroxides, the Fe oxides, the Fe hydroxides, and metal oxides (MOs), and the metal oxides (MOs) include mixed oxides, where M is Ti, Nb, Mn, Si, V, or a combination thereof excluding Cr and Fe, and O means oxygen.
[0054] Although examples of metal oxides (MOs) have been listed above, it should be noted that these are merely examples to aid in understanding the present invention and do not particularly limit the technical concept of the present invention.
[0055] The total oxides and hydroxides include Cr oxide, Cr hydroxide, Fe oxide, Fe hydroxide, and the above metal oxides (MO).
[0056] The reason for limiting the range of photoelectron takeoff angles in X-ray angle-resolved photoelectron spectroscopy will be explained below, followed by the reason for limiting the ranges of the surface oxide element ratios (1) and (2).
[0057] In X-ray angle-resolved photoelectron spectroscopy, the lower the take-off angle of photoelectrons, the smaller the analysis depth from the outermost surface of stainless steel in the depth direction, and the larger the take-off angle, the larger the analysis depth. In consideration of this, according to the present invention, in order to analyze the composition of oxides formed on the nm-thick surface of stainless steel, the surface of stainless steel was measured by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source at a photoelectron take-off angle of 12°.
[0058]
[0059] As described above, the reason why the surface oxide element ratio (1) value is limited to 0.5 to 5 is that if it is less than 0.5, the Fe element, which is disadvantageous to corrosion resistance, becomes a solid solution in Cr in the form of an oxide, and the surface potential of the material becomes 2 eV or less, and Fe dissolution is high in the fuel cell operating environment, which may cause a decrease in cell performance. If the (1) value is 5 or more, the Cr content in the surface oxide becomes relatively high, which prevents ohmic contact due to uneven contact between the oxide layer and the base material interface layer, acts as a factor of poor conductivity, and creates semiconductor characteristics with a band gap energy of 2 eV or more, resulting in poor electrical conductivity. In consideration of the through-surface electrical conductivity and corrosion resistance, it is more preferable to control the oxide layer to 0.7 to 4.
[0060] The reason why the surface oxide element ratio (2) value measured under the above conditions is limited to 0.5 or less is because it is the limit at which the passivation film changes from a semiconducting property to a conducting property. If the surface oxide element ratio (2) value exceeds 0.5, the passivation film cannot secure sufficient through-surface electrical conductivity due to its semiconducting property, making it unsuitable for use as a stainless steel for fuel cell separators.
[0061] As described above, by controlling the surface oxide element ratio (2) value to 0.5 or less, the present invention can control the band gap energy of the surface oxide layer to 2 eV or less. If the band gap energy is 0 eV, the surface oxide layer has conductive properties, and if the band gap energy is more than 0 eV and 2 eV or less, the surface oxide layer has intermediate properties between conductive and semiconductive properties, making it suitable for use as stainless steel for fuel cell separators.
[0062] Furthermore, according to the present invention, it is preferable to control the surface oxide element ratio (1) value to 0.44 or less so that the band gap energy of the surface oxide layer is 0 eV. The fact that the band gap energy of the surface oxide layer is 0 eV means that the surface oxide layer forms a new ohmic contact with the stainless steel base material, which was not known before, despite being a passive film layer composed of oxides. In other words, it means that the surface oxide layer has become a new conductive film layer that can form an ohmic contact with the stainless steel base material.
[0063] The stainless steel for a fuel cell separator according to the present invention, which has excellent through-surface electrical conductivity and corrosion resistance, is not particularly limited as long as the band gap energy of the surface oxide layer is 2 eV or less and the surface corrosion potential is 0.2 V. As an example, austenitic, ferritic, and ferritic-austenitic two-phase stainless steels can be used for the stainless steel of the present invention.
[0064] In addition, the composition of the stainless steel for a fuel cell separator having excellent through-surface electrical conductivity and corrosion resistance according to the present invention is not particularly limited. However, the preferred composition is as follows. However, it should be noted that the following composition is merely an example to aid in understanding the present invention and does not limit the technical concept of the present invention.
[0065] The steel sheet according to one embodiment may contain, in weight percent, C: more than 0% and not more than 0.02%, N: more than 0% and not more than 0.02%, Si: more than 0% and not more than 0.25%, Mn: more than 0% and not more than 0.2%, P: more than 0% and not more than 0.04%, S: more than 0% and not more than 0.02%, Cr: 15 to 34%, the balance being Fe and other unavoidable impurities. In the following, unless otherwise specified, the unit is weight percent (wt%).
[0066] C: 0% over 0.02% or less, N: 0% over 0.02% or less
[0067] C and N combine with Cr in steel to form stable Cr carbonitrides, which may result in the formation of areas locally deficient in Cr and reduce corrosion resistance, so the lower the content of both elements, the better. Therefore, in the present invention, the content of C and N may be added in the range of C: more than 0% and 0.02% or less, and N: more than 0% and 0.02% or less.
[0068] Si: more than 0% less than 0.25%
[0069] Silicon is an effective element for deoxidization. However, when added in excess, it reduces toughness and formability, and the SiO2 oxide generated during the annealing process reduces electrical conductivity and hydrophilicity. In consideration of this, the content of silicon in the present invention may be more than 0% and less than 0.25%.
[0070] Mn: More than 0% and less than 0.2%
[0071] Mn is an effective element for deoxidization. However, MnS, which is an inclusion of Mn, reduces corrosion resistance, so the content of Mn in the present invention can be more than 0% and 0.2% or less.
[0072] P: More than 0% and less than 0.04%
[0073] Since P reduces not only the corrosion resistance but also the toughness, the P content in the present invention may be added in an amount of more than 0% and not more than 0.04%.
[0074] S: More than 0% and less than 0.02%
[0075] S combines with Mn in steel to form stable MnS, which acts as a starting point for corrosion and reduces corrosion resistance, so the lower the S content, the better. In consideration of this, the S content in the present invention may be added in an amount of more than 0% and not more than 0.02%.
[0076] Cr: 15~34%
[0077] Cr is an element that improves corrosion resistance. Cr is added to ensure corrosion resistance in the strongly acidic environment in which fuel cells operate. However, when added in excess, it reduces toughness. Taking this into consideration, the Cr content in the present invention may be added at 15-34%.
[0078] In addition, in addition to the above-mentioned alloy composition, the steel sheet according to one embodiment may contain, as optional alloy components, one or more of V: more than 0% and not more than 0.6%, Ti: more than 0% and not more than 0.5%, and Nb: more than 0% and not more than 0.5%, in weight percent, if necessary.
[0079] V:0 exceeds 0.6% or less
[0080] V is an element that inhibits the dissolution of Fe in the fuel cell operating environment and improves the life characteristics of the fuel cell. However, when added in excess, it reduces toughness. Taking this into consideration, the V content in the present invention may be added in a range of more than 0% to 0.6%.
[0081] TI: More than 0% and less than 0.5%, Nb: More than 0% and less than 0.5%
[0082] Ti and Nb are elements that improve corrosion resistance by suppressing the formation of areas where Cr is locally depleted by combining with C and N in steel to form stable carbonitrides. However, when added in excess, it reduces toughness, so in consideration of this, the contents of Ti and Nb in the present invention may be added such that Ti is more than 0% and 0.5% or less, and Nb is more than 0% and 0.5% or less.
[0083] The remaining component is iron (Fe). However, in a normal manufacturing process, unintended impurities may be inevitably mixed in from the raw materials or the surrounding environment, and it is not possible to exclude these. Since any engineer of a normal manufacturing process would know about the impurities, the entire contents of the impurities will not be mentioned in this specification.
[0084] The present invention will be described in more detail with reference to the following examples. However, it should be noted that the following examples are merely for illustrating and explaining the present invention in more detail, and are not intended to limit the scope of the present invention, as the scope of the present invention is determined by the matters described in the claims and matters reasonably inferred therefrom.
[0085] <Example>
[0086] Steels having the composition in Table 1 below were produced into slabs through a steelmaking-continuous casting process. The produced slabs were then hot-rolled at 1200°C to produce hot-rolled steel sheets with a thickness of 4.5 mm. The hot-rolled steel sheets were heated at 1050°C, and then repeatedly cold-rolled and bright annealed at 1000°C in a 100% hydrogen reducing atmosphere to produce cold-rolled steel sheets with a thickness of 0.15 mm.
[0087] [Table 1]
[0088] As shown in Table 2 below, in this example, the cold rolled steel sheet manufactured in Table 1 was dissolved in a 150 g / L sulfuric acid solution to adjust the time of the first surface modification step (incubation process), and hydrogen peroxide was added to the same solution to increase the surface potential to adjust the time of the surface modification step (passivation process). The surface oxide element ratios (1) and (2) in Table 2 are values derived from the following formulas (1) and (2), and are values derived when the surfaces of the invention examples and comparative examples are measured by X-ray angle resolved photoelectron spectroscopy using an Al-Kα X-ray source at a photoelectron takeoff angle of 12° as shown in Table 2.
[0089] TIFF0007640699000010.tif16134
[0090] TIFF0007640699000011.tif16134
[0091] The surface oxide element ratios (1) and (2) were measured using the following method: First, the analysis was performed using a PHI Quantera II instrument, and the analysis results were used to separate the peaks at the binding energies of metal oxides (MO), Cr oxides, Cr hydroxides, Fe oxides, and Fe hydroxides using CasaXPS software, and the atomic concentrations were calculated using this.
[0092] The "sum of atomic concentrations (at%) of metal elements in total oxides and hydroxides" in the surface oxide element ratio value of the surface oxide element ratio was calculated by adding the "sum of atomic concentrations (at%) of metal elements in metal oxides (MO)" described above, the sum of the atomic concentrations (at%) of Cr in Cr oxides and Cr hydroxides, and the sum of the atomic concentrations (at%) of Fe in Fe oxides and Fe hydroxides.
[0093] The sum of the atomic concentration (at%) of Cr in Cr oxide and Cr hydroxide was calculated by separating the peaks at the binding energies of Cr oxide and Cr hydroxide, and fitting them to the Cr 2p spectrum to derive the sum of the atomic concentration (at%) of Cr. The sum of the atomic concentration (at%) of Fe in Fe oxide and Fe hydroxide was calculated by separating the peaks at the binding energies of Fe oxide and Fe hydroxide, and fitting them to the Fe 2p spectrum to derive the sum of the atomic concentration (at%) of Fe. The "sum of atomic concentrations (at%) of metal elements in metal oxides (MO)" was calculated by separating the peaks at the binding energies of metal oxides (MO), and fitting them to the spectrum of each metal (M) to derive the sum of the atomic concentrations (at%) of metal elements. Here, metal oxides (MO) include mixed oxides, M is an alloy element or combination thereof in the base material except Cr and Fe, and O means oxygen.
[0094] The band gap energy in Table 2 means the band gap energy of the surface oxide layer. The band gap energy of the surface oxide layer was measured using a Current Sensing Atomic Force Microscope (Keysight 9500 model). The stainless steel of the invention example and comparative example were cut to 1 cm x 1 cm to prepare test pieces, and the band gap energy was measured in a current probe mode with a bias of -10V to 10V applied with a load of 20 nN in a nitrogen atmosphere with a relative humidity of 18% so that the surface oxide layer was measured in an inactive state. The band gap energy was measured five times in an area of 50 μm x 50 μm, and the width of the area where the current detected when the bias was changed from -10V to 10V was the band gap energy. In this case, a silicon tip with a platinum coating of 30 nm thickness was used as the probe.
[0095] In order to secure the surface properties of stainless steel as in this embodiment, first, the MO oxide formed on the surface layer due to the constituent elements of the base alloy elements (Cr, Mn) must be removed, and then the conductive oxide (Cr, Fe) must be reformed. Conventionally, the process of removing the oxide is called the incubation stage, and the process of reforming the conductive oxide is called the passivation stage.
[0096] The incubation process time required varies depending on the composition of the steel, and it can be seen that the more elements such as Mn, Si, Nb, Ti, and V there are in the steel, the longer the incubation process time is required. This is because these elements facilitate the formation of surface oxides, so it takes time to remove the oxides composed of these elements. Also, the higher the Cr content, the higher the Cr oxide ratio in the surface layer, which reduces the rate at which such oxides are formed, and so there is a tendency for the incubation process time to decrease. The passivation process time can be controlled by changing the total surface treatment time and can be changed depending on the Cr content.
[0097] As a result of confirming through the examples, when the incubation process time is longer than the formula (1), the oxide formed on the surface layer can be effectively removed, and when the passivation process time is longer than the value of the formula defined in the formula (2), the band gap energy of the surface oxide layer is 2 eV or less, and the surface potential is 0.2 V (vs. saturated calomel electrode) or more, and an oxide with excellent conductivity and corrosion resistance that is stably secured can be formed.
[0098] (1) Incubation process time (seconds) ≧3x[Mn]+15x[Si+Ti]+10x[Nb+V]-0.05x[Cr]
[0099] (2) Passivation process time (seconds) ≧0.8x[Cr]
[0100] In the above formula, Mn, Si, Ti, Nb, V, and Cr are values in weight percent.
[0101] FIG. 1 shows the results of comparing the band gap energy of the surface oxide layer between Comparative Example 6 and Example 6.
[0102] Comparative Example 6 has a surface oxide layer with a band gap energy of 7.6 eV, which shows semiconductor properties, while Example 6 has a surface oxide layer with a band gap energy of 0 eV. The fact that the surface oxide layer has a band gap energy of 0 eV means that, despite being a passive film layer made of oxide, the stainless steel base material and the surface oxide layer form a new ohmic contact that was not known before. In other words, the surface oxide layer has become a new conductive film layer that can form an ohmic contact with the stainless steel base material.
[0103] FIG. 2 is a diagram showing the incubation process time and the passivation process time for Example 6. The passivation process time is the time during which the potential is increased and maintained from the point when the surface potential becomes 0.2 V (vs. saturated calomel electrode) or more.
[0104] FIG. 3 is a diagram showing the incubation process time and the passivation process time for Comparative Example 6.
[0105] Meanwhile, as in Example 6, the incubation process time required varies depending on the composition of the steel, and it can be seen that the more elements such as Mn, Si, Nb, Ti, and V are present in the steel, the longer the incubation process time is required. This is because these elements facilitate the formation of oxides on the surface layer, and it takes time to remove the oxides composed of these elements. The passivation process time can be controlled by changing the total surface treatment time, and can vary depending on the Cr content, and it can be seen that the treatment time becomes longer as in Example 6.
[0106] FIG. 4 shows the results of observing Si, Mn, Nb, and V oxides when the surface of Example 6 is measured by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source at a photoelectron takeoff angle of 12°.
[0107] FIG. 5 shows the results of observing Si, Mn, Nb, and V oxides observed when the surface of Comparative Example 6 is measured by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source at a photoelectron takeoff angle of 12°.
[0108] It can be seen that the metal oxide (MO) oxide observed in Example 6 is lower than that in Comparative Example 6.
[0109] [Table 2]
[0110] Although exemplary embodiments of the present invention have been described above, the present invention is not limited thereto, and it should be understood that various changes and modifications can be made by those skilled in the art without departing from the concept and scope of the following claims. [Industrial Applicability]
[0111] The stainless steel for fuel cell separators according to the present invention has excellent through-surface electrical conductivity and corrosion resistance, and is therefore industrially applicable.
Claims
1. A stainless steel for a fuel cell separator having excellent through-surface electrical conductivity and corrosion resistance, characterized in that, when the surface of the stainless steel containing 15% by weight or more of Cr is measured by X-ray angle-resolved photoelectron spectroscopy using an Al-Kα X-ray source at a photoelectron take-off angle of 12°, the measured surface oxide element ratio (1) value is 0.5 to 5, and the measured surface oxide element ratio (2) value is 0.5 or less. Here, Cr oxide is Cr 3 O 4 , Cr 2 O 3 , CrO 2 or CrO 3 The Cr hydroxide means CrOOH, Cr(OH) 2 Or Cr(OH) 3 The iron oxides are FeO, Fe 2 O 3 Or Fe 3 O 4 and Fe hydroxide means FeOOH. The total oxides and hydroxides include the Cr oxides, the Cr hydroxides, the Fe oxides, the Fe hydroxides, and metal oxides (MO), and the metal oxides (MO) include mixed oxides, where M is Ti, Nb, Mn, Si, V, or a combination thereof excluding Cr and Fe, and O means oxygen.
2. 2. The stainless steel for a fuel cell separator plate having excellent through-surface electrical conductivity and corrosion resistance according to claim 1, characterized in that the band gap energy of the surface oxide layer of the stainless steel is 2 eV or less.
3. 2. The stainless steel for a fuel cell separator having excellent through-surface electrical conductivity and corrosion resistance according to claim 1, wherein the surface oxide layer of the stainless steel forms an ohmic contact with a base material.
4. 2. The stainless steel for a fuel cell separator having excellent through-surface electrical conductivity and corrosion resistance according to claim 1, wherein the surface passivation potential of the stainless steel is 0.2 V or more.
Citation Information
Patent Citations
Stainless steel for separator of solid polymer fuel cell and its manufacturing method, and solid polymer fuel cell using that stainless steel
JP2004149920A
Stainless steel sheet having excellent surface electrical conductivity, and method for producing the same
JP2008285731A
Stainless steel separator for fuel cell and method of manufacturing the same
JP2009263794A
Sheet stainless steel for separators in solid polymer fuel cells, and solid polymer fuel cells using the same
JP2010138487A
Stainless steel separator for fuel cell and manufacturing method thereof
JP2013065562A